Dampak Hibah Pariwisata terhadap Kinerja Industri Pariwisata Jawa Tengah dan Daerah Istimewa Yogyakarta - Nunik Nugraheni; Kezia Stephanie; Khresna Bayu Sangka; Jalu Aji Prakoso; Rochman Hadi Mustofa (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2021)
The sustainability of the tourism industry, especially hotels and restaurants in Central Java and Special Region Yogyakarta during the Covid-19 pandemic, is very crucial to be maintained and improved because it has a simultaneous impact on social and economic conditions. Through the policy of financial stimulation for hotel and restaurant tourism industry players, it is hoped that these businesses can survive when the number of tourist visits decreases and prepare for recovery efforts when new habits are implemented, including in tourism industry activities through the distribution of tourism grants. Considering that the allocation of grant funds is expected to provide stimulation and adjustment to new habits of the tourism industry, an empirical study using the approach of Quantitative Efficiency Analysis with Frontier Analysis (FA) and Structural Equation Modeling (SEM) for 116 hotel and restaurant tourism actors, shows that the provision of Tourism Grants in the Province of Central Java and Special Region Yogyakarta has a positive effect, especially on the efficiency of the allocation of financial performance obtained from the allocation of employee salaries and operational costs to increase output efficiency in the form of hotel and restaurant receipts.